2017
DOI: 10.5830/cvja-2016-084
|View full text |Cite
|
Sign up to set email alerts
|

Persistent left superior vena cava

Abstract: SummaryPersistent left superior vena cava (PLSVC) is the most common congenital malformation of thoracic venous return and is present in 0.3 to 0.5% of individuals in the general population. This heart specimen was dissected from a 35-yearold male cadaver whose cause of death was determined as non-cardiac. The heart was examined and we found a PLSVC draining into the coronary sinus. The right superior vena cava was present with a small-diameter ostium. An anomalous pulmonary vein pattern was observed; there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 23 publications
0
66
0
5
Order By: Relevance
“…Dilatation of the coronary sinus in case of persistent left SVC due to the increased blood flow in the sinus has been previously described in the literature . However, in this different hemodynamic situation, the venous drainage through the right SVC is decreased, which could explain the smaller diameter of the right SVC . The smaller size of the aorta could be explained by the high association with left ventricular outflow tract obstructions such as anomalies of the aortic arch and aortic valve.…”
Section: Discussionmentioning
confidence: 87%
“…Dilatation of the coronary sinus in case of persistent left SVC due to the increased blood flow in the sinus has been previously described in the literature . However, in this different hemodynamic situation, the venous drainage through the right SVC is decreased, which could explain the smaller diameter of the right SVC . The smaller size of the aorta could be explained by the high association with left ventricular outflow tract obstructions such as anomalies of the aortic arch and aortic valve.…”
Section: Discussionmentioning
confidence: 87%
“…of Tyrak et al. (), the sinuatrial valve is essentially normal and the sinus septum is remodelled, as indicated by the beam of tissue visible between the Eustachian valve and the coronary sinus (Tyrak et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…(), the sinuatrial valve is essentially normal and the sinus septum is remodelled, as indicated by the beam of tissue visible between the Eustachian valve and the coronary sinus (Tyrak et al. ). However, the specimen with a persistent left superior caval vein that we examined did not show a clear sinus septum, there was no beam between the Eustachian valve and coronary sinus, suggesting that, in this case, the sinus septum may have remodelled to the point that it had been lost.…”
Section: Resultsmentioning
confidence: 99%
“…The diagnosis of PLSVC may be confirmed by injecting agitated saline into a peripheral vein on the left arm with subsequent visualization of the small bubbles (agitated saline) in the coronary sinus before entering the right atrium. [1][2][3] Other imaging modalities to confirm the diagnosis include contrast venography, computed tomography, and three-dimensional enhanced magnetic resonance venography.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is the most common congenital anomaly of the thoracic venous return, a persistent left superior vena cava (PLSVC) has a reported incidence of less than 0.5% in the general population. [1][2][3][4] The incidence is higher (10-12%) in association with other forms of congenital heart disease, most commonly atrial (ASD) and ventricular septal defects. PLSVC results from a failure of obliteration of the left common cardinal vein during embryological development.…”
Section: Introductionmentioning
confidence: 99%